Special educational needs : a guide for inclusive practice - Peer, Lindsay; Reid, Gavin (Eds.) (b, 2021)
This guide to inclusive practice covers contemporary policy issues, perspectives from practice and specialist guidance from across a wide range of common syndromes. Bringing together the important combination of theory, knowledge and practice, each chapter is written by experts from fields within Special and Additional Educational Needs. This third edition includes new chapters on: The current context of SEN current context: in research and practice -- Speech, language and communication -- The role and use of technology in supporting learners with SEND -- Pathological/Extreme Demand Avoidance (PDA/EDA) -- Working together -- Children and Young People's Perspectives. Providing a solid foundation for understanding and supporting learners with additional needs, this comprehensive text is ideal for students, teachers or practitioners. -- Provided by publisher
Includes bibliographical references and index.
Keywords: Children with disabilities Education; Education, Special